Cerita Bimo Suci: Suatu Tinjauan Filosofis Muslimah - nok muslimah (Jurnal CULTURE (Culture, Language, and Literature Review), 2016)
This study entitled “Cerita Bimo Suci Suatu Tinjauan Filsafat” which discusses about Bimo suci letters, one of the Javanese literature that reveals the teachings of philosophy. The objectives of the study are to know and to describe the letters of Bimo suci seeing from the ontology, epistemology and axiology. The approach of the study is descriptive qualitative which analyzes the data through library research. The result shows that the letters of Bimo suci contain the high values of philosophy, particularly about morality, life and living. It also reveals the actions related to the real moral values which always obtain various trials, especially when the moral values are put into practice in everyday life.  The significance of the study is that the philosopical values contained in the letters of Bimo suci would be understandable, useful and practice in real life.    Keywords: Bimo suci letter, ontology, epistemology, axiology